Virus Particles and Virus-like Particles-based Vaccines for Cancer Treatment - Li, Zijie (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Virus vaccines in cancer immunotherapy are a promising area in cancer treatments, utilizing viruses to augment the immune response against cancer cells and induce tumor cell death. Oncolytic virotherapy known as virus-based vaccine is an innovative cancer treatment leading by oncolytic virus (OVs) which has shown encouraging outcomes over the last twenty years. This therapy is able to effectively combine with other therapy, for instance radiotherapy and car-t cell therapy. Virus-like particles (VLPs) serve as an antigen presentation platform in cancer therapeutic and preventive applications. Compared with oncolytic virus vaccines, VPLs-based vaccines can directly uptake by immune cells without any infection. Initial virus-based and virus-like particle-based cancer treatments have shown little effectiveness, but progress in molecular engineering, genomics, and molecular analysis offer hope for improving and rejuvenating virus-vaccines in medical settings. However, there are still obstacles like OVs delivery and VLPs modifications in preclinical or clinical trials. It is crucial to figure out the research status and the difference of OVs-based and VLPs-based vaccines.